Urban environments and objectively-assessed physical activity and sedentary time in older Belgian and Chinese community dwellers: potential pathways of influence and the moderating role of physical function - Ester Cerin; Delfien Van Dyck; Casper J. P. Zhang; Jelle Van Cauwenberg; Poh-chin Lai; Anthony Barnett (BMC, 2020)
Abstract Background Many studies have examined neighbourhood environmental correlates of older adults' physical activity (PA) but only a few focused on sedentary time (ST). Only a small proportion of these studies used objective measures of PA/ST, such as accelerometer-assessed PA/ST, and only a couple employed accelerometer cut-points appropriate for older adults. Furthermore, although older adults experience declines in physical function as they age, there is a dearth of information on the impact of the neighbourhood environment on PA/ST in individuals with different levels of physical function. Methods We used data from two extant cross-sectional studies conducted in Hong Kong (China) and Ghent (Belgium) (N = 829). Participants were recruited from pre-selected administrative units stratified by socio-economic status and walkability. Moderate-to-vigorous PA (MVPA) and ST were assessed for 7 days using accelerometers and cut-points developed for older adults. Objective neighbourhood environmental attributes within 400 m and 1 km buffers surrounding participants' homes were quantified using Geographic Information Systems data. Lower extremity physical function was objectively assessed. Socio-demographic information was collected via interviews. Total, direct and indirect (mediated) effects of environmental attributes on MVPA and ST were estimated using generalised additive mixed models and the joint-significant test. Results Commercial/civic destination density and number of parks within 1 km from home showed positive total and direct effects on MVPA, and public transport density showed negative total and direct effects on ST, which were consistent across cities and physical function levels. The total and direct effects of residential density on MVPA depended on physical function, and those of residential density on ST differed by city. A complex network of potential inconsistent pathways linking all environmental attributes to MVPA and ST in the whole sample or in subgroups of participants was revealed. Discussion Access to parks and commercial/civic destinations appear to support older adults' MVPA in different geographical and cultural contexts and irrespective of their physical function level. By supporting MVPA, these characteristics also contribute to a reduction in ST. The potential effects of public transport, recreational facilities and residential density are less straightforward and point at inconsistent effects that may depend on the geographical context and level of physical function.